MAO: a very short introduction - Davin, Delia (Oxford, 2013)
Few would doubt that Mao Zedong was a major figure of 20th century Asian history. In this Very Short Introduction Delia Davin chronicles the fascinating story of Mao's life. From peasant child to founder of the Chinese Communist Party and ruler of the world's most populous nation, she considers the major events of his life, exploring his revolutionary writings, and his utopian dreams that culminated in the events of the Cultural Revolution. Davin presents Mao in all his complexity ruthless, brutal, and ambitious, a man of enormous talent and perception, yet a leader who remains detested by some and acclaimed by others.
Keywords: Organising revolution